457 The Impact of PAP Therapy on Hematocrit in OSA and Polycythemia: A Pilot Study. (3rd May 2021) - Jafri, Mustafa; Rosa-Acosta, Gabrielle; Martinez, Jose Flores; Schofield, Elizabeth; Wilkins, Cy; Mulhall, John; Tan, Miranda
Abstract: Introduction: Untreated polycythemia leads to complications including thrombosis. Obstructive sleep apnea (OSA) is commonly associated with secondary erythrocytosis, which testosterone therapy can perpetuate. Effects of positive airway pressure (PAP) on elevated hematocrit (HCT) is unknown. We hypothesize PAP adherence can reduce HCT in men with OSA and polycythemia. Methods: Retrospective chart review of male outpatients with newly diagnosed OSA and HCT≥45% at or 3 months before polysomnography (PSG) was conducted. Intervention group consisted of patients initiating PAP for OSA. HCT within 6 months of PAP initiation and PSG were recorded for intervention and control groups, respectively. Primary endpoint was time-to-HCT reduction of HCT<50% plus 3% decrease. Cox proportional-hazards analysis was used to assess time-to-HCT response. Demographics, smoking history, testosterone administration, STOP-Bang score, AHI, and PAP compliance data were obtained. Patients excluded if PAP not indicated, or if PSG, PAP compliance, or repeat HCT were unavailable. Results: 41 men with OSA had HCT≥45%, of which 16 had HCT≥50%. Median age was 60 years and median BMI was 32 kg/m2. 28 started PAP. 21 met definition for PAP compliance within 6 months. Median AHI of intervention and control groups were 23 and 19 events/hr, respectively. Mean baseline HCT of both groups were 49 and 50, respectively. No significant difference in age, BMI, smoking history, testosterone therapy, and baseline HCT between both groups noted. 39% of intervention group exhibited HCT response at 1 or more longitudinal assessments, versus 38% of control. Intervention group had higher mean STOP-Bang than control (mean 5.9 vs. 4.6, p=0.01) and trended towards higher mean baseline AHI (27.4 vs. 19.0, p= 0.06). Time-to-event analysis controlling for STOP-Bang and AHI demonstrated PAP was not associated with time-to-HCT response (HR = 1.3, 95% CI = 0.4–4.4). In moderate-severe OSA patients, 40% of intervention group had HCT response compared to 14% of control, though difference was not significant (HR = 2.5, 95% CI = 0.3–20.0). Conclusion: Moderate-severe OSA patients trended towards reduction in HCT with PAP, although not statistically significant. Testosterone administration did not affect HCT response to PAP in this cohort. Larger studies are required to determine HCT response to PAP in these patients. Support (if any):